THE VITALITY OF HUNTINGTON’S “SOLDIER’S MIND” – ARE THE CADETS OF THE MILITARY ACADEMY CONSERVATIVE? - Starčević, Srđan (Political Review, 2026)
Seven decades ago, Samuel P. Huntington proposed a theory of civil-military relations, the foundation of which are the professional military ethics of officers, which are typically conservative in their principles and values. It simultaneously allows officers to practice their profession (which is in direct contact with politics), command the army (which is one of the institutions of the political system), and participate in the execution of tasks (which are part of the war effort or preparations for war, the essence of which is political). Since then, the dominant social values have changed significantly, especially after the collapse of the USSR and the dominance of neoliberal capitalism. The armies of numerous European states have been reformed. The important question is whether the values of the officer profession have changed and liberalized in order to align with dominant social values or whether Huntington’s conservative military mind is resisting the challenges of the times. In this paper, the vitality of Huntington’s theoretical explanation of officer professionalism is proven by empirical research on the attitudes of cadets of the Military Academy in Belgrade, which indicate their conservatism. The cadets’ attitudes are aligned with the traditional values of the army and its social role. At the same time, they are in contradiction with the dominant social values of fluid modernity. The research results show a homogeneity of the cadets’ responses, which are largely unaffected by their socio-demographic characteristics. They also point to one truth: the officer profession mainly attracts young people with a conservative attitude. This may perhaps explain some of the problems in attracting more young people to enroll in military schools and serve in the military, which almost all armies in Europe are facing today.